2013
DOI: 10.1186/cc12831
|View full text |Cite
|
Sign up to set email alerts
|

Patients with sepsis exhibit increased mitochondrial respiratory capacity in peripheral blood immune cells

Abstract: IntroductionIn sepsis, mitochondria have been associated with both initial dysfunction and subsequent upregulation (biogenesis). However, the evolvement of mitochondrial function in sepsis over time is largely unknown, and we therefore investigated mitochondrial respiration in peripheral blood immune cells (PBICs) in sepsis patients during the first week after admission to the intensive care unit (ICU).MethodsPBICs from 20 patients with severe sepsis or septic shock were analyzed with high-resolution respirome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 31 publications
2
64
2
1
Order By: Relevance
“…For example, Belikova et al found that maximal oxygen consumption in the presence of uncoupler was decreased (though SRC was not explicitly calculated) and the fraction of LEAK respiration was increased compared to healthy controls (18). In contrast to these findings, however, Sjovall et al demonstrated a progressive increase in basal and maximal respiration in adult PBMCs on day 1–2 through day 6–7 of sepsis compared to healthy controls (21). These contradictory findings may stem from methodological variability between studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, Belikova et al found that maximal oxygen consumption in the presence of uncoupler was decreased (though SRC was not explicitly calculated) and the fraction of LEAK respiration was increased compared to healthy controls (18). In contrast to these findings, however, Sjovall et al demonstrated a progressive increase in basal and maximal respiration in adult PBMCs on day 1–2 through day 6–7 of sepsis compared to healthy controls (21). These contradictory findings may stem from methodological variability between studies.…”
Section: Discussionmentioning
confidence: 88%
“…However, direct evidence for mitochondrial dysfunction in human studies is limited, largely due to the impracticality of tissue biopsies in critically ill patients (15, 16). Several studies have shown that alterations in mitochondrial respiration in peripheral blood mononuclear cells (PBMCs)—monocytes and lymphocytes--are associated with disease severity, immune suppression, and mortality (1721). Under quiescent conditions, PBMCs rely more on mitochondrial respiration than glycolysis to meet metabolic demands and exhibit a substantial SRC (2224).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the prominence of NADH dehydrogenase activity in the top gene networks is consistent with decreased complex I gene expression [56] and activity noted in skeletal muscle in human adult sepsis [57,58]. Prior studies using blood samples from patients with sepsis have also demonstrated altered respiratory chain activity in peripheral blood mononuclear cells and platelets [9,11,13,59,60].…”
Section: Discussionmentioning
confidence: 66%
“…35 Furthermore, mitochondrial dysfunction has been implicated as a possible causative mechanism for the reduced activity of immune cells in sepsis. 36 …”
Section: Pathophysiologymentioning
confidence: 99%